Low Dose Aspirin in high-risk pregnancies: The volatile effect of acetylsalicylic acid on the inhibition of platelets uncovered by G. Born's light transmission aggregometry. (June 2021) - Stern, C.; Mayer-Pickel, K.; Weiss, E.-C.; Kutllovci-Hasani, K.; Nanda, M.; Eberhard, K.; Cervar-Zivkovic, M.; Prüller, F.
Highlights: The optimal Aspirin dosage for the prevention of preeclampsia has to be individualized. Platelet inhibition by Aspirin varies individually between pregnant women. Increasing Aspirin to 150 mg daily does not necessarily magnify the inhibitory effect. Optical aggegrometry is used to monitor Aspirin effectiveness in women at risk. Abstract: Preeclampsia still represents a life-threatening pregnancy complication, associated with severe maternal and neonatal morbidity and mortality. Low-dose Aspirin is advised to avoid preeclampsia in high-risk pregnancies worldwide. As Aspirin does not cover all women at risk, the prescription raises questions concerning optimal target population, dosage, and onset of therapy. The aim of this study was to test platelet responsiveness on Aspirin by optical aggegrometry, to gain robust biochemically assessment data of Aspirin in an obstetric cohort. 248 women at high risk for development of preeclampsia were included in the study. Aspirin-prophylaxis was administered either in 100 mg (n = 229) or 150 mg (n = 90) daily. Dosing of 100 mg Aspirin was maintained if testing revealed a sufficient platelet inhibition. If platelet inhibition was insufficient, dosage was increased to 150 mg Aspirin and re-testing was advised. 91 patients (91/229 = 39.7%) presented a sufficient inhibitory Aspirin effect at a dosage of 100 mg, but in 138 patients LTA showed an inadequate Aspirin response (138/229 = 60.3%). In 19 women 150 mg Aspirin was administered as starting dose due to new recommendations. Of all women at 150 mg Aspirin 64 did not properly respond (35.4%). The overall rate of sufficient responding women regardless the Aspirin dose was 64.6%. This study demonstrates still an insufficient inhibition of platelet aggregation in about 1/3 of women even with a dosage of 150 mg Aspirin daily, who might potentially benefit from further increase. These data show, that there is a need for further research to allow a personalized approach for individualized Aspirin therapy, maximizing the preventive benefit for mother and child.